Thermal stress analysis and residual stresses in a thermoplastic composite beam - Sayman, O; Belevi, M; Duranay, M (Sage Publications Ltd, 2003)
In this study, an elastic-plastic thermal stress analysis is carried out on a steel fibre reinforced thermoplastic matrix composite beam. Temperature is chosen to vary linearly, that is zero and T-o at the upper and lower surfaces, respectively. The beam is fixed by two rigid planes at the ends. The solution is performed at 0degrees, 45degrees, 60degrees, 75degrees and 90degrees orientation angles. Plastic yielding is not obtained for 30degrees orientation angle. The plastic region is expanded at the lower side of the beam. It is found that the intensity of the residual stress component of sigma(x) and the equivalent plastic strain are maximum at the lower surface of the beam. The residual stress is found to be greatest for 0degrees orientation angle. The intensity of the equivalent plastic strain is the greatest for 45degrees orientation angle. In addition, for the same plastic distribution, the intensity of the transverse displacement is the largest for that orientation angle.